Supplementary Data Tables 1 from Immunogenomic Landscape of Neuroendocrine Prostate Cancer - Bhavneet Bhinder (14963342) (2025)
Suppl Table S1. Clinical characteristics of metastatic patient cohortSuppl Table S2. The 361 gene signature identified in this study to classify T-cell immune clustersSuppl Table S3. The 80 immune and stroma related gene signatures used to quantify the TMESuppl Table S4. DEGs for SCLC versus NEPC tumorsSuppl Table S5. NCI-Nature_2016 pathways enriched in the DEGs from SCLC vs NEPC